TANGGAP WABAH COVID-19 BERSAMA WARGA DUSUN SINGOSAREN RT 06 RW 05, KALURAHAN SINGOSARI, KECAMATAN MOJOSONGO, BOYOLALI - SRI LESTARI; ADHIPUTRO PANGARSO WICAKSONO (KULTURA DIGITAL MEDIA ( Research and Academic Publication Consulting ), 2021)
One of the main points of Tridharma Perguruan Tinggi is to regulate tertiary institutions to solve problems in the community including through the community service activities, this activity is called Kuliah Kerja Nyata orsimply KKN. However, the type of KKN activity held this time is slightly different from the previous generation KKN because it was carried out during the covid-19 virus pandemic. Various efforts have been made to prevent the transmission and spread of the covid-19 virus which has plagued our lives, one of which is the work program proposed by the Singosaren Village Community Service group, namely response to the Covid-19 outbreak and student learning assistance. The method used in this service consists of the first four stages of students observing the mobility of community activities during a pandemic. The second stage, students prepare media that will be used as an effort to prevent Covid-19. The preparations include planting family medicinal plants (toga), making disinfectants, making a poster warning about Covid-19 and suggesting a place to wash hands. The third stage, students and residents carry out activities in Singosaren village such as installing posters in public areas and installing hand washing facilities and carrying out activities.